65th Annual International Federation of Library Associations (IFLA) Conference, Bangkok, Thailand - Julia Gelfand (Issues in Science and Technology Librarianship)
The article provides highlights of the 65th Annual International Federation of Library Associations (IFLA) Conference in Bangkok, Thailand.